2013
DOI: 10.1021/nn403847z
|View full text |Cite
|
Sign up to set email alerts
|

Membranes with Highly Ordered Straight Nanopores by Selective Swelling of Fast Perpendicularly Aligned Block Copolymers

Abstract: Membranes with uniform, straight nanopores have important applications in diverse fields, but their application is limited by the lack of efficient producing methods with high controllability. In this work, we reported on an extremely simple and efficient strategy to produce such well-defined membranes. We demonstrated that neutral solvents were capable of annealing amphiphilic block copolymer (BCP) films of polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) with thicknesses up to 600 nm to the perpendicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
203
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(223 citation statements)
references
References 59 publications
3
203
1
11
Order By: Relevance
“…For example, using 500 nm porous PS-b -P2VP fi lms Yin et al [ 98 ] created titania nanotubes as shown in Figure 7 d and e. An important process step for this accomplishment is related to the "reactivity" of the PS-b -poly-x-vinylpyridine (x = 2 or 4) containing BCPs. As mentioned in Section 3.1, when exposed to selective solvents, PVPs swell and form pores.…”
Section: Atomic Layer Deposition Methods and Block Copolymer Templatesmentioning
confidence: 99%
“…For example, using 500 nm porous PS-b -P2VP fi lms Yin et al [ 98 ] created titania nanotubes as shown in Figure 7 d and e. An important process step for this accomplishment is related to the "reactivity" of the PS-b -poly-x-vinylpyridine (x = 2 or 4) containing BCPs. As mentioned in Section 3.1, when exposed to selective solvents, PVPs swell and form pores.…”
Section: Atomic Layer Deposition Methods and Block Copolymer Templatesmentioning
confidence: 99%
“…Such metastability makes it possible to force the alignment of the nanostructures without tuning the energy balance, and the glassy nature of the final film insures the long-term absence of evolution of the pattern. Solvent swelling was proven to be a useful process to reach perpendicular alignment of cylinders in different systems [61][62][63][64] (cf. Fig.…”
Section: Solvent Annealingmentioning
confidence: 99%
“…4.5). This process is however still considered difficult to reproduce, mainly because reproducibility requires a precise mastering and controlling of many experimental [65], annealing time with characteristic times sometimes shorter than 1 min [63], vapor pressure and the rate of vapor removal [39,66], glass transition temperature. All these can affect, often in coupled ways, the resulting metastable morphologies.…”
Section: Solvent Annealingmentioning
confidence: 99%
“…For example, thin films of block polymers can be prepared by coating a solution onto a solid substrate followed by complete solvent evaporation and annealing to an equilibrium nanostructure. In order to induce porosity, the thin film may undergo selective swelling in the melt followed by extraction of the swelling agent [38][39][40] or a sacrificial moiety may be etched to create the percolating network of pores necessary for filtration. 35,[41][42][43] The nanostructured thin film is then transferred onto a mechanically stable support for transport characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Since this seminal study, several other efforts have used this approach to generate key insights into the use of nanoporous block polymer thin films based on cylindrical morphology as filters. 38,40,[50][51][52][53][54][55] Scalable fabrication of high performance block polymer membranes The self-assembled nanostructure of block polymers at equilibrium demonstrated their promise as next-generation membranes. However, the translation of these materials to functional membrane systems required more than a well-ordered nanostructure on the surface.…”
Section: Introductionmentioning
confidence: 99%